Inovasi Pestisida Nabati Berbasis Daun Pepaya untuk Meningkatkan Pertanian Ramah Lingkungan di Desa Sememu Kabupaten Lumajang - Desfianto Akbar Perkasa; Syachillah Samy Qadriyyah; Niken Ayu Arthafany; Septi Rahayu; Aisya Rahani Salputri; Destri Aulia Wulandari; Muflikhatun Nikmah; Ariva Nawiriyah Putri; Defi Nugraheni; Ricky Kurniawan; Diana Lulita; Roihan Firdaus; Mohammad Nurul Huda (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The agricultural sector plays a strategic role in ensuring national food security, particularly in rural areas where the majority of the population depends on agricultural production. Sememu Village, an agricultural-based community with rice and tobacco as its primary commodities, has faced recurring pest attacks in recent years. Conventional pest control methods in the area have primarily relied on chemical pesticides. However, excessive and prolonged use of these chemicals has resulted in serious problems, including pest resistance, environmental contamination, and potential health risks to farmers and consumers. This study aims to improve farmers’ knowledge and practical skills by introducing an alternative, eco-friendly approach through a training program on the production of botanical pesticides derived from papaya leaves (Carica papaya L.). Papaya leaves are known to contain bioactive compounds such as papain, chymopapain, alkaloids, terpenoids, and flavonoids, which exhibit natural insecticidal properties. The training activities consisted of initial observation, presentation of scientific and practical materials, hands-on practice in the preparation of botanical pesticides, and field testing on rice and tobacco plants. The findings demonstrated that the use of papaya leaf-based pesticides effectively reduced pest feeding activity and increased pest mortality rates, thereby minimizing crop damage. Importantly, this approach did not cause harmful effects on the surrounding ecosystem. The program highlights the potential of botanical pesticides as a sustainable solution for integrated pest management in agricultural villages, contributing both to environmental conservation and farmers’ welfare.